Foods and dietary supplements in the prevention and treatment of disease in older adults - Watson, Ronald Ross (Amsterdam Academic Press, 2015)
"Foods and Dietary Supplements in the Prevention and Treatment of Disease in Older Adults focuses on the ways in which food and dietary supplements affect the major health problems of aging adults. Researchers in nutrition, diet, epidemiology, and aging studies, as well as healthcare providers who work with elderly patients will use this comprehensive resource as a tool in their long-term goal of preventing and treating chronic disease within the elderly"--Provided by publisher.
Keywords: Older people -- Nutrition; Functional foods; Dietary supplements